GROWTH RESPONSE OF Ganoderma sp. MYCELIUM TREATED WITH ROOT EXUDATES OF HERBACEOUS PLANTS - Rahmadhani, Tiara Putri; Suwandi, Suwandi; Pujiastuti, Yulia (BIOVALENTIA: Biological Research Journal, 2018)
The purpose of the study was to study response of Ganoderma sp. that were given exudate treatment of plant roots. Ganoderma sp. is a pathogen that causes stem rot at base of oil palm. In addition to oil palm this fungus can attack hard and woody crops such as coconut, rubber, tea, cocoa etc. Isolate used is Ganoderma sp. Bio-10197 code obtained from Phytopathology laboratory SEAMEO BIOTROP Bogor. Mycelium Ganoderma sp. reproduced in malt agar media until mycelium grows over agar surface. Ganoderma mycelium was inoculated on 1x1x5 cm rubber wood pieces for 14 days until the mycelium grew over rubber sticks. The exudate used from ganyong (Canna edulis Kerr), garut (Maranta arundinacea Linn.), Ginger (Zingiber officinale Rosc.), Turmeric (Curcuma domestica Val.), Galangal (Alpinia galanga (L.) Sw.) and lidah mertua (Sansevieria trifasciata). The design used in this study was a complete randomized design (RAL) with 7 treatments consisting of 5 repeatations. The results of this study indicate that the mycelium experienced inhibition of growth, especially in the treatment of root exudate galangal shown by 60,81% percentage and tongue-in-law with a percentage of 59,58% colonization. On observation of growth characteristics of mycelium Ganoderma sp. visible zone delimited in the form of a brown mycelium pile suspected as an indication of mycelium rejection of bioactive compounds contained exudate.